TIME AS A COGNITIVE DOMINANT IN FORMATTING THE POINT OF VIEW IN JOSTEIN GAARDER’S FICTION - Natia Tolordava, (International Journal of Innovative Technologies in Social Science, 2022)
The article is about the bestseller of the Norwegian writer Jostein Gaarder’s novel “The Orange Girl” and tells about intertextual searches in Gaarder's work. Emphasizes the writer's ability: to speak lightly, even a little naively, and in an interesting way about the most difficult, to "understand" the reader in interacting with himself, which is the most important of the many possibilities that literature offers. At the same time, it is no coincidence that the genre of Jostein Gaarder’s “The Orange Girl” is supplemented and defined as the mystery novel.